2011
DOI: 10.1007/s10826-011-9541-5
|View full text |Cite
|
Sign up to set email alerts
|

Connecting the Dots: Stages of Implementation, Wraparound Fidelity and Youth Outcomes

Abstract: Wraparound is a family-driven, youth guided, team-based process for planning and implementing services and supports (Miles et al. 2006). The National Wraparound Initiative (NWI) has identified ten elements of wraparound (i.e., family voice and choice, team based, natural supports, collaborative, community based, culturally competent, individualized, strengths based, persistence and outcomes based) and four phases through which teams consisting of the identified youth, his/her parents or caregivers, family memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 16 publications
1
19
0
Order By: Relevance
“…For example, although evidence for concurrent and construct validity has now been produced, association with child and family outcomes has not yet been attempted, as has been done for the WFI (Bruns et al, 2005; Cox et al, 2010; Effland et al, 2011). Given the small sample sizes, replication of the findings showing differences in results for different types of raters will be important to attempt in the near future.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, although evidence for concurrent and construct validity has now been produced, association with child and family outcomes has not yet been attempted, as has been done for the WFI (Bruns et al, 2005; Cox et al, 2010; Effland et al, 2011). Given the small sample sizes, replication of the findings showing differences in results for different types of raters will be important to attempt in the near future.…”
Section: Discussionmentioning
confidence: 99%
“…A multiple regression indicated positive relationships between WFI scores at baseline and child behavioral strengths six months later as measured by the Behavioral and Emotional Rating Scale (Epstein & Sharma, 1998), after controlling for baseline characteristics (Bruns et al, 2005). Another study (Effland et al, 2011) found positive relationships between WFI-4 scores and changes in scores on a standardized measure of functioning – the Child and Adolescent Needs and Strengths tool (Lyons, Weiner, & Lyons, 2004). Intraclass Correlation for all three respondents has been found to be .51, indicating good inter-respondent agreement for a scale of this nature (Bruns et al 2009).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A multiple regression indicated positive relationships between WFI-2 scores at baseline and child behavioral strengths six months later as measured by the Behavioral and Emotional Rating Scale (Epstein & Sharma, 1998), after controlling for baseline characteristics (Bruns, Suter, Force, & Burchard, 2005). Another study found positive relationships between WFI-4 scores and a decrease in youth needs (Effland, Walton, & McIntyre, in press), as measured by the Child and Adolescent Needs and Strengths measure (Lyons, Weiner, & Lyons, 2004). Studies have also found positive correlations between WFI scores and system factors theorized to be associated with successful wraparound implementation (Bruns, Suter, & Leverentz-Brady, 2006; Effland, et al, in press).…”
Section: Methodsmentioning
confidence: 99%
“…Poor implementation of wraparound has been credited for some of the inconsistencies in findings on youth satisfaction with wraparound obtained to the present. 5,6,23 Although evidence bearing directly on challenges to wraparound implementation with transition-age youth is limited to date, two types of concerns can be raised. First, it may be more difficult to involve family and other supports when working with youth transitioning to adulthood than with younger youth, as these relationships among older youth are frequently strained and disengaged.…”
Section: Challenges Of Wraparound With Youth Transitioning To Adulthoodmentioning
confidence: 99%